Formation and evolution of the local interstellar environment: combined constraints from nucleosynthetic and X-ray data. Issue 4 (11th September 2020) - Fujimoto, Yusuke; Krumholz, Mark R; Inutsuka, Shu-ichiro; Boss, Alan P; Nittler, Larry R
ABSTRACT: Several observations suggest that the Solar system has been located in a region affected by massive stellar feedback for at least a few Myr; these include detection of live 60 Fe in deep-sea archives and Antarctic snow, the broad angular distribution of 26 Al around the Galactic plane seen in all-sky γ-ray maps, and the all-sky soft X-ray background. However, our position inside the Galactic disc makes it difficult to fully characterize this environment, and our limited time baseline provides no information about its formation history or relation to large-scale galactic dynamics. We explore these questions by using an N -body + hydrodynamics simulation of a Milky-Way-like galaxy to identify stars on Sun-like orbits whose environments would produce conditions consistent with those we observe. We find that such stars are uncommon but not exceptionally rare. These stars are found predominantly near the edges of spiral arms, and lie inside kpc-scale bubbles that are created by multiple generations of star formation in the arm. We investigate the stars' trajectories and find that the duration of the stay in the bubble ranges from 20 to 90 Myr. The duration is governed by the crossing time of stars across the spiral arm. This is generally shorter than the bubble lifetime, which is ∼100 Myr as a result of the continuous gas supply provided by the arm environment.